PERANCANGAN SIMULASI TIMBANGAN DIGITAL MENGGUNAKAN SENSOR HX711 DENGAN TAMBAHAN BUZZER BERBASIS ESP32 - Rachmawati, putri (MEDIKA TRADA : Jurnal Teknik Elektomedik Polbitrada, 2023)
As technology advances, equipment that previously operated analogue is now being developed using digital techniques, and equipment that was previously manual is starting to become automatic. Digital scales are measuring instruments for measuring the mass of an object or substance with a digital display. This simulation was created with the aim of producing an ESP32 based digital weighing device, using HX711 as a load sensor and displaying load values using a 16x2 type LCD. This makes measurement results easier to read and more accurate than analog scales.